DOES HYPERCHOLESTOLEMIA PREDISPOSE TO ROTATOR CUFF PATHOLOGIES? - LK, SUNIL; U KAMATH, SURENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Background: Rotator cuff tear are one of most common orthopedic musculoskeletal problem gaining importance due to large health scale expenditure. Causes of rotator cuff tears are multifactorial and unclear. Previous studies have suggested relation between elevated serum lipid profile and rotator cuff tear in western population. We therefore undertook study in our Indian population to correlate association of hypercholesterolemia with rotator cuff tear. Objective: To find association of rotator cuff pathology with hypercholesterolemia in Indian patients. Materials and methods: After obtaining clearance from institutional ethics committee. We prospectively collected fasting lipid samples of population who came to our hospitals with complaints of shoulder pain during our study period. 50 patients had rupture of rotator cuff which was confirmed by ultrasound of involved shoulder. 50 were seen for non-cuff related complaints. We followed strict inclusion and exclusion criteria. Results: Total cholesterol, Triglycerides and low density lipoprotein concentration of patients with rotator cuff tendon tear were on higher side than control group. High density lipoprotein trend showed being lower than control group. 21 of 50 (42%) had high cholesterol (total cholesterol greater than 240mg/dl) than compared to 18 of 50 (36%) in control group. however P value=0.539 and showed no statistical significance between groups. Conclusion: In Indian population there was no correlation between hypercholesterolemia and rotator cuff tear which is statistically significant. Key words Rotator cuff tear, Hypercholesterolemia, Indian population.